THE RELATIONSHIP BETWEEN MATERNAL KNOWLEDGE AND THE ROLE OF HEALTH WORKERS ON STUNTING HANDLING IN THE UPT POLONIA HEALTH CENTER AREA IN 2023 - Petra Yoseppina Saragih; Martaulina Sinaga; Indra Agussamad; Petra Diansari Zega; Anggreni Simatupang; Desy Surya Sartika (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Background: Toddlers, namely the golden age period, are important periods in the process of human growth and development. According to the World Health Organization (WHO), stunting is a chronic nutritional problem in toddlers characterized by shorter height compared to other children . One of the factors that can influence the incidence of stunting is the lack of knowledge of mothers about stunting which causes children to be at risk of failure to grow and develop. Objective: This study aims to determine the picture of the level of knowledge of mothers about stunting in the UPT Polonia Health Center Area in 2023. Method: This research is qualitative with descriptive method. The respondents in this study were mothers who had toddlers at the Posyandu of Madras Hulu sub-district Results: The results of the study found that the average education of respondents was in the junior high school category and the most dominant level of knowledge was at the medium level of knowledge. Keywords: Knowledge Level, Stunting, Mothers of toddlers.